To solve the equation, we first distribute the numbers inside the parentheses:
2(x + 7) = 3(x + 3)
2x + 14 = 3x + 9
Now, we want to isolate the variable x on one side of the equation. We can do this by moving all terms involving x to one side of the equation and all constants to the other side. Let's subtract 2x from both sides:
2x + 14 - 2x = 3x + 9 - 2x
14 = x + 9
Now, subtract 9 from both sides:
14 - 9 = x + 9 - 9
5 = x
Therefore, the solution to the equation 2(x + 7) = 3(x + 3) is x = 5.
What is the solution to the equation `2\left(x+7\right)\ =\ 3\left(x+3\right)`?
1 answer